Meiotic Studies in Some Medicinal Angiosperms from Doaba Region of Punjab, India - Kuljinder Kaur,; MC Sidhu, (International Journal of Phytomedicine, 2014)
The chromosome number and their behavior in 15 medicinal plant species collected from Doaba region of Punjab, India have been studied. The species have shown chromosome numbers like Basella rubra L. (n=22), Coccinia cordifolia Cogn. (n=12), Delphinium ajacis L. (n=8), Lens culinaris Medic. (n=7), Melilotus alba Desr. (n= 8), Nicotiana plumbaginifolia Viv. (n=10), Nymphoides cristata (Roxb.) Kuntze (n=9), Papaver rhoeas L. (n=7), Raphanus sativus L. (n=9), Sesamum indicum L (n=13), Tinospora cordifolia (Wild.) Hook.f.et Thoms. (n=13), Triticum aestivum L. (n=21), Vitex negundo L. (n=17), Xanthium strumarium L. (n=18) and Zea mays L. (n=10). Most of the species are diploid with normal course of meiosis. But meiotic abnormalities in the form of univalents, stickiness and presence of supernumerary B-chromosomes have also been observed in some species. All the species have some medicinal value. The chromosome counts in these species are in conformity with the earlier reports, but behavioral changes have been observed in some species. This shows the genetic stability and resistance of these species to various biotic and abiotic stresses.